Nilai Tambah Ekonomi Pemanfaatan Sampah - Annisa Dewi Akbari; Didien Suhardini; Tiena Gustina Amran; Dadang Surjasa; Agung Sasongko (Abdimas Universal, 2024)
The waste problem is still a big problem in Indonesia. One of them can be seen at the Cipayung Final Disposal Site (TPA), West Java, which is currently overloaded. The amount of household waste produced is not commensurate with the capacity of the landfill. Therefore, community participation is very necessary in overcoming the waste problem. Seeing this condition, the residents of the Barazaki Housing Depok plan to start sorting and utilizing waste. However, unfortunately, based on the results of interviews with RT heads, there are still many residents of Barazaki Housing who have not sorted and utilized their waste. This is due to a lack of knowledge regarding how to sort and utilize waste both technically and economically. Many residents do not know the fact that waste can generate additional economic income so they are not motivated to sort or utilize waste. This PkM aims to realize a program for sorting and processing household waste with the economic value of the results of processing household waste. The method used is education regarding waste sorting and utilization, both technically and economically. The result of this PkM activity is that the majority of Barazaki housing residents understand that waste can provide added economic value and they are willing to sort and process inorganic and organic waste. PkM participants were very enthusiastic because the content of the PkM counseling was very interesting and useful, the material was delivered well, and the objectives of the PkM activities were clearly conveyed.